Crossing the river : a memoir of the American left, the Cold War, and life in East Germany - Grossman, Victor, 1928-; Solomon, Mark. (Amherst : University of Massachusetts Press, 2003)
Faced with an accusation from the US Army's highest legal authority in 1952, Grossman left his unit stationed in Bavaria and swam the Danube to East Germany. He traces his childhood and experiences as a student, worker, and soldier; then describes life in his new home among a surprisingly large community of defectors. There is no index. Annotation (c)2003 Book News, Inc., Portland, OR (booknews.com).
Crossing the border. Childhood -- Harvard years -- Working -- Soldier. Life in East Germany. Starting in a new land -- The clubhouse and the lathe -- A student again -- Journalist in a divided city -- Radio, Robeson, and the Prague Spring -- Freelancing in East Germany -- Tremors -- Death of a nation -- A new life in united Germany -- The Big Rock Candy Mountain? -- Epilogue : eau de cologne -- Afterword and selected bibliography by Mark Solomon.
Includes bibliographical references.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
eBooks on EBSCOhost
Keywords: Grossman, Victor, -- 1928-; Grossman, Victor, -- 1928-; Grossman, Victor; Defectors -- United States -- Biography; Defectors -- Germany (East) -- Biography; Cold War; Germany (East) -- Description and travel; Transfuges -- États-Unis -- Biographies; Transfuges -- Allemagne (Est) -- Biographies; Guerre froide; BIOGRAPHY & AUTOBIOGRAPHY / General; Defectors; Travel; Germany (East); United States; Ost-West-Konflikt; Deutschland; USA; Biographies; Electronic books